Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kantor Samsat Kota Tabanan - Novitasari, Ni Luh Gde; Santosa, Made Edy Septian; Putri, Ni Putu Eka Aristya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Taxes are a major source of state revenue used to finance national development and improve public welfare. Motor Vehicle Tax (PKB) is a type of regional tax that contributes significantly to regional original revenue. Taxpayer compliance in paying motor vehicle tax is a critical factor in determining the success of regional tax revenue. However, many taxpayers still fail to fulfill their tax obligations, necessitating various efforts to improve compliance. One such step taken by the government is the implementation of the drive-thru Samsat (Vehicle Registration System) system, which aims to streamline services for taxpayers, increase taxpayer awareness, enforce strict tax sanctions, implement tax outreach, and improve service quality. This study aims to determine the effect of the drive-thru Samsat system, taxpayer awareness, strict tax sanctions, tax outreach, and service quality on motor vehicle taxpayer compliance at the Tabanan City Samsat Office. The population of this study was all taxpayer vehicles registered at the Tabanan City Samsat Office. The sample size for this study was 100 taxpayers, determined using the accidental sampling method. The analytical tool used to test the hypotheses was multiple linear regression. The results of the study show that the Samsat drive-thru and tax socialization have a positive effect on taxpayer compliance, while taxpayer awareness, the firmness of tax sanctions and the quality of service do not have an effect on taxpayer compliance.